Always at war : organizational culture in Strategic Air Command, 1946-62 - Deaile, Melvin G. (Transforming war, 2018)
"Always at War is the story of Strategic Air Command (SAC) during the early decades of the Cold War. It explains how an organization dominated by experienced World War II airmen developed a unique culture that thrives to this day. The narrative begins with the origins of powered flight and describes how the early generation of American pilots developed their own culture and shared beliefs rooted in the promise of airpower."--Provided by publisher.